Participation and politics in transboundary hydropower development: the case of the Pak Beng Dam in Laos - Suhardiman, Diana; Geheb, K. (Wiley, 2022)
Hydropower development in the lower Mekong Basin is being rapidly developed. Taking the Pak Beng hydropower project in Laos as a case study, this paper looks at participation and politics in transboundary hydropower development, how the latter is revealed by multiple, parallel institutional architectures in hydropower decision-making across scales, and its implications for transboundary environmental governance. We look at the institutional disjuncture in hydropower decision-making, how it is (re)produced by powerful, albeit conflicting narratives at respectively national and transboundary levels, power relations shaping these narratives, and how these translate into local community's limited ability to convey their voices and represent their development needs. Conceptually, the paper sheds light on the underlying politics in transboundary environmental governance by bringing to light the structural factors that prevent participation, including how these factors are justified, sustained and to a certain extent reproduced as an integral part of legal, policy, and institutional landscapes that govern hydropower decision-making across scales (e.g., local to transboundary).